The clot thickens: an incompletely ligated left atrial appendage. Issue 2 (June 2018) - Thomas, Merrill; Grodzinsky, Anna; Zink, Martin
Summary: Our patient presented with known mechanical mitral valve endocarditis documented by 2D transesophageal echocardiogram (TOE) from a recent hospitalization at an outside facility. On admission to our center, there was no prior knowledge of an incompletely ligated left atrial appendage (LAA) according to patient- or family-reported history, review of outside records or the outside facility's 2D TOE report. A 3D TOE performed at our center to assess her pathology, since a month had passed from her prior hospitalization, revealed a LAA ligation with evidence of communication to the left atrium and with clot present in the appendage. This case report highlights the common finding of incomplete closure of the LAA following surgical ligation, thus making it inadequate for stroke prevention in patients with atrial fibrillation, and that 3D TOE plays a valuable role in assessing the durability of LAA ligation. Learning points: 3D transesophageal echocardiography (TOE) is a valuable tool in assessing the durability of left atrial appendage (LAA) ligation given the superior image granularity as compared with 2D TOE. LAA ligation may not be adequate for stroke prevention in patients with atrial fibrillation as incomplete closure is common following surgical ligation. LAA occlusion should be considered in these cases.